Atypical calcification of uterine myomata in 66-year-old female – case report and review of the literature - Sobkiewicz, Sławomir (Menopause Review/Przegląd Menopauzalny, 2003)
Calcification of uterine myomata in 66-year-old female – case report and review of the literature The female, aged 66, was admitted to the Clinical Hospital with the following diagnosis: Uterus myomatosus. Pyometra. A typical hysterosalpingo-oophorectomy was performed. After cutting the uterine wall, irregular formations 5–20 mm in diameter, resembling coarse gravel, were found. The histopathological investigation of the excised uterus revealed: Leiomiomata parva multiplicia calcinificata in lumine cavi uteri. The course of retrogressive changes occurring in the uterine myomata leading to their calcification is rare. It seems that the process leading to the lesions observed by us must have lasted at least over ten years and must have been preceded by progressive necrotic changes.